STEM careers: Workshops using role model can reduce gender stereotypes - Katharina Drescher; Simone Häckl; Julia Schmieder (DIW Weekly Report, 2020)
Women continue to be underrepresented in STEM occupations (science, technology, engineering, and math). Based on a survey among secondary school students in Vienna, we show, for instance, that girls' career aspirations, interests, and self-assessed skills in STEM fields are related to gender stereo- types. Parents also play a crucial role in this context. Further results indicate that a half-day career guidance workshop, which confronts students with role models, can change gender-biased attitudes towards technology. This demonstrates that short, inexpensive interventions can be an effective way of fostering girls' interest in STEM.
Keywords: I24; J16; 330; STEM; gender stereotypes; role models